The genesis of Mordenite occurrences: Diagenetic and hydrothermal alteration processes of Paleocene volcanics in Ilıca (Yıldızeli), Türkiye - Hülya Ateş (Bulletin of the Mineral Research and Exploration)
Different geological processes such as weathering, diagenesis in hydrological systems, hydrothermal processes and contact metamorphism have been proposed to explain the genetic relationships of mordenite occurrences. The mineralogical and genetic analyses in this study are essential for identifying alteration minerals and assessing reaction processes. The Yıldızeli region, located south of the İzmir-Ankara-Erzincan suture zone and northeast of the Kırşehir block, is significant for its mineral deposits. This area consists of Paleocene-Miocene volcano-sedimentary units. Analyse results of selected zone mordenite samples from the Paleocene volcanic units that host mordenite mineralization are linked to low-grade metamorphism, particularly associated with zeolite facies (150-300 °C, 1-3 kbar and pH 4-7), following tectonically controlled hydrothermal alteration. The zeolitization process involves interacting fluids crucial for mobilizing alkali elements, withcompositional variations in mordenite indicating a continuous evolution toward equilibrium conditions under decreasing temperatures. The progression from mordenite to smectite, along with associated kaolinite occurrences, can be attributed to the hydrothermal circulation of alkaline waters and sodium extraction from underlying evaporites.